Spline Nonparametric Regression to Analyze Factors Affecting Gender Empowerment Measure (GEM) in East Java - Mahfiroh, Luluk; Farida, Yuniar (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
Gender is a multidimensional issue that's not limited to gender discrimination, but alsoincludes the economic, educational, and health aspects, which then become the focus of almost all the Sustainable Development Goals (SDGs). Evaluation of the development devoted to the perspective of the gender using several indicators, Gender Development Index (GDI) and Gender Empowerment Measure (GEM). GEM describes the role of women in the economic sphere and is measured by equality in political participation. GEM of East Java for 5 consecutive years (2014 â€“ 2018) is lower than the average national GEM. This study aims to identify factors affecting GEM in East Java using nonparametric regression spline quadratic. The result ofthe regression model shows the factors affecting GEM East Java is the Labor Force Participation Rate(LFPR) population of women (), School Participation Rate(SPR) high school population of women (), Percentage of Population Female thatWorking in the formal sector (), sex ratio (), Percentage of Population Female that Working as members of Peopleâ€™s Representative Council (), Percentage of Population Female that working as Civil Servants (), and rate of women's income donations (). The model generatesÂ value of 93.74% and MAPE of 3.22%.This research contributes to the implementation of non-parametric spline regression in identifying various factors that influence social phenomena.